Beyond the Headlines: Public Health Implications of Law Enforcement's Excessive Use of Force. (November 2015) - Resnick, Beth A.; Edwards, Kathleen F.; Rutkow, Lainie
Abstract : This commentary discusses public health implications of law enforcement's excessive use of force.